A review of orchid pollination studies in China. Issue 4 (13th January 2014) - TANG, Guang‐Da; OU, Jing‐Hui; LUO, Yi‐Bo; ZHUANG, Xue‐Ying; LIU, Zhong‐Jian
Abstract Orchid pollination and evolution are common topics in evolutionary biology. China has approximately 1400 orchid species distributed in diverse habitats and account for approximately 5% of the orchid species in the world. These orchids provide us with materials to explore coevolution and organic evolution. We summarized 53 Chinese orchid pollination studies and synthesized their main findings and common patterns. Bees and flies are the main pollinators of Chinese orchids and drive the diversification of Paphiopedilum and Cypripedium. In addition, the patterns are consistent with phylogenetic evolution studies. Almost half of the Chinese orchids use a common food‐deceptive pollination strategy to transfer their pollens. Other orchids use Batesian mimicry, brood‐site imitation, and green‐leaf volatile imitation, which is rare. Holcoglossum amesianum (Rchb. f.) Christenson and Paphiopedilum parishii (Rchb. f.) Stein, which live in insect‐scarce habitats, use self‐pollination strategies to ensure their reproductive success. However, studies on pollination are in the early stages and comprehensive studies are scarce. Therefore, future studies should involve additional disciplines and techniques, such as chemecologic, electrophysiologic, genomic, transcriptomic, and proteomic methods, to evaluate the floral features that attract specific pollinators and to elucidate the patterns of Chinese orchid pollination, evolutionary history, diversification, and speciation between orchids and their pollinators.